PENGARUH MEDIA PRESENTASI INTERAKTIF DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR FISIKA PADA PESERTA DIDIK SMA KRISTEN GAMALIEL MAKASSAR - Yonathan Sapan; M. Sidin Ali; Muhammad Arsyad (UNM Journal of Technology and Vocational, 2023)
This research is a pure experimental research using a 2×2 factorial design which aims to: (1) describesignificant differences in physics learning outcomes between students who are given interactivepresentation media and conventional media, (2) analyze significant differences in physics learningoutcomes between participants students who are given interactive presentation media andconventional media, for students who have high learning motivation, (3) analyze differences in physicslearning outcomes of students who are given interactive presentation media and conventional media,for students who have low learning motivation, (4) analyze the effect of the interaction betweeninteractive presentation media and learning motivation on students' physics learning outcomes. Thisresearch was carried out at Gamaliel Makassar Christian High School with the stages of observation,preparation of research tools and instruments, content and empirical validation, provision ofmotivational questionnaires, application of learning media to experimental and control classes,administration of final tests which were then analyzed to test hypotheses. The results of the hypothesistest showed (1) overall, there were differences in the physics learning outcomes of students who weregiven interactive presentation media with conventional media, (2) for students who had highmotivation to learn physics, there were significant differences in physics learning outcomes betweenstudents who given interactive presentation media with conventional media, (3) for students who havelow motivation to learn physics, there is a significant difference in physics learning outcomes betweenstudents who are given interactive presentation media with conventional media, (4) there is nointeraction between learning media and motivation to learn about physics learning outcomes ofstudents.